Chemisorption, Morphology, and Structure of a n‐Type Perylene Diimide Derivative at the Interface with Gold: Influence on Devices from Thin Films to Single Molecules. Issue 9 (21st January 2015) - Ciccullo, Francesca; Savu, Sabine‐Antonia; Gerbi, Andrea; Bauer, Maximilian; Ovsyannikov, Ruslan; Cassinese, Antonio; Chassé, Thomas; Casu, Maria Benedetta
Abstract We have investigated thin films of a perylene diimide derivative with a cyano‐functionalized core (PDI‐8CN2) deposited on Au(111) single crystals from the monolayer to the multilayer regime. We found that PDI‐8CN2 is chemisorbed on gold. The molecules experience a thickness‐dependent reorientation, and a 2D growth mode with molecular stepped terraces is achieved adopting low deposition rates. The obtained results are discussed in terms of their impact on field effect devices, also clarifying why the use of substrate/contact treatments, decoupling PDI‐8CN2 molecules from the substrate/contacts, is beneficial for such devices. Our results also suggest that perylene diimide derivatives with CN bay‐functionalization are very promising candidates for single‐molecule electronic devices.